Highly efficient scavenging of Cr(VI) by two-dimensional titanium carbide nanosheets: kinetics, isotherms and thermodynamics analysis - Yinzhi Lv (IWA Publishing, 2021)
In this study, two-dimensional (2D) MXene material (Ti3C2Tx) was employed to investigate its potentials toward the Cr(VI) removal in aqueous system by batch experiments. Characterization techniques such as SEM-EDS, HRTEM, XRD, FI-TR and XPS were used to analyze the structure and interaction of Ti3C2Tx before and after Cr(VI) adsorption. The results indicated that the layered structure of Ti3C2Tx had unique surface functional properties and abundant active sites, such as –OH, Ti–O, C = O, which exhibited high adsorption capacity for Cr(VI) removal. The Cr(VI) adsorption capacity by Ti3C2Tx decreased with the increase of pH, and its maximum value can reach 169.8 mg/g at pH = 2.0. The adsorption kinetic was well-explained by a pseudo-second-order kinetic, indicating that chemical interaction played a dominant role in the adsorption of Cr(VI) on Ti3C2Tx. Meanwhile, the isotherm data was calculated to conform to the Freundlich isotherm model. Thermodynamic analysis indicated that the adsorption process of Cr(VI) on Ti3C2Tx was a spontaneous endothermic process. These experimental results revealed that Ti3C2Tx had tremendous potential in heavy metals adsorption from aqueous solutions. HIGHLIGHTS Novel Two-dimensional titanium carbide nanosheets (Ti3C2Tx MXene) were employed for Cr(VI) scavenging.; Ti3C2Tx MXene exhibited high adsorption ability for the Cr(VI) removal, namely 169.8 mg/g at pH = 2.0.; The adsorption of Cr(VI) on Ti3C2Tx MXene is a multilayer adsorption and spontaneous endothermic process.; The chemical interaction played a dominant role in the Cr(VI) removal by Ti3C2Tx MXene.;